Pain relief in a neuropathy patient by lacosamide: Proof of principle of clinical translation from patient-specific iPS cell-derived nociceptors - Namer, Barbara; Schmidt, Diana; Eberhardt, Esther; Maroni, Michele; Dorfmeister, Eva; Kleggetveit, Inge Petter; Kaluza, Luisa; Meents, Jannis; Gerlach, Aaron; Lin, Zhixin; Winterpacht, Andreas; Dragicevic, Elena; et al. (EBioMedicine, 2018)
BACKGROUND: Small fiber neuropathy (SFN) is a severe and disabling chronic pain syndrome with no causal and limited symptomatic treatment options. Mechanistically based individual treatment is not available. We report an in-vitro predicted individualized treatment success in one therapy-refractory Caucasian patient suffering from SFN for over ten years. METHODS: Intrinsic excitability of human induced pluripotent stem cell (iPSC) derived nociceptors from this patient and respective controls were recorded on multi-electrode (MEA) arrays, in the presence and absence of lacosamide. The patient's pain ratings were assessed by a visual analogue scale (10: worst pain, 0: no pain) and treatment effect was objectified by microneurography recordings of the patient's single nerve C-fibers. FINDINGS: We identified patient-specific changes in iPSC-derived nociceptor excitability in MEA recordings, which were reverted by the FDA-approved compound lacosamide in vitro. Using this drug for individualized treatment of this patient, the patient's pain ratings decreased from 7.5 to 1.5. Consistent with the pain relief reported by the patient, microneurography recordings of the patient's single nerve fibers mirrored a reduced spontaneous nociceptor (C-fiber) activity in the patient during lacosamide treatment. Microneurography recordings yielded an objective measurement of altered peripheral nociceptor activity following treatment. INTERPRETATION: Thus, we are here presenting one example of successful patient specific precision medicine using iPSC technology and individualized therapeutic treatment based on patient-derived sensory neurons.
EVALuna2:35119

Pattern of Functional TTX-Resistant Sodium Channels Reveals a Developmental Stage of Human iPSC- and ESC-Derived Nociceptors - Eberhardt, Esther; Havlicek, Steven; Schmidt, Diana; Link, Andrea; Neacsu, Cristian; Kohl, Zacharias; Hampl, Martin; Kist, Andreas; Klinger, Alexandra; Nau, Carla; Schüttler, Jürgen; Alzheimer, Christian; et al. (Stem Cell Reports, 2015)
Human pluripotent stem cells (hPSCs) offer the opportunity to generate neuronal cells, including nociceptors. Using a chemical-based approach, we generated nociceptive sensory neurons from HUES6 embryonic stem cells and retrovirally reprogrammed induced hPSCs derived from fibroblasts. The nociceptive neurons expressed respective markers and showed tetrodotoxin-sensitive (TTXs) and -resistant (TTXr) voltage-gated sodium currents in patch-clamp experiments. In contrast to their counterparts from rodent dorsal root ganglia, TTXr currents of hPSC-derived nociceptors unexpectedly displayed a significantly more hyperpolarized voltage dependence of activation and fast inactivation. This apparent discrepancy is most likely due to a substantial expression of the developmentally important sodium channel NAV1.5. In view of the obstacles to recapitulate neuropathic pain in animal models, our data advance hPSC-derived nociceptors as a better model to study developmental and pathogenetic processes in human nociceptive neurons and to develop more specific small molecules to attenuate pain.
EVALuna2:2465